Faktor-Faktor Yang Mempengaruhi Kunjungan Ibu ke Posyandu Nagari Kayu Tanam Kabupaten Padang Pariaman Menggunakan Analisis Faktor - Putri Anisah; Helma Helma (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — Posyandu is a health service provided by the government for the community. Of the many mothers who have babies or toddlers, and pregnant women are of the opinion that the visit to the posyandu has no effect on their children. This study aims to determine the factors that influence the mother's visit to Posyandu Nagari Kayu Tanam, Padang Pariaman. This study aims to determine the factors that influence the mother's visit to the Posyandu Nagari Kayu Tanam, Padang Pariaman. This type of research is applied research using primary data obtained from the results of filling out the questionnaire. The population in this study were all mothers who have babies or toddlers and 133 pregnant women in Nagari Kayu Tanam, Padang Pariaman. The sampling technique is total sampling. There are two factors that influence the mother's visit to the Posyandu Nagari Kayu Tanam, namely, external factors consisting of distance from the posyandu, family support, and the role of cadres. Internal factors consist of mother's attitude and posyandu facilities.Keywords — posyandu, factor analysis, total sampling.